Peculiarities of the motion of the pseudorelativistic Dirac quasiparticles in the alpha-T3 model with the step-like barrier - Korol, Anatoliy; Medved, Nataliya (My University, 2020)
Within the continuous approach, the transmission coefficient T of the Dirac quasielectrons through a step-like potential barrier in the a-T3 model is calculated and analyzed. It is believed that the degree of coupling of the central atom with the atoms in the vertices of the hexagonal lattice is characterized by the parameter a, which can acquire values from zero to one. Particular attention is given in the work to intermediate values of a, since, it is known from the literature, that they are important for observing a lot of physical phenomena. The wave functions as well as the transmission ratio are sought by the Dirac type equation. The Hamiltonian of the system is represented by a spinor of 9 components, which is expressed, in particular, by the parameter a The transmission coefficient is found by means of matching of wave ftmctions at heterojunctions. In particular, it is found that there is a range of problem parameters, such as the height of the electrostatic barrier U, the energy of the quasielectrons E, the ratio of the Fermi velocities in the barrier and out-of-barrier areas (3, in which the value of the transmission coefficient reaches maximum, that is, it is close to unity for a values close to unity. In this area, the dependence of the transmission coefficient on the value of a is weak. When the value of a becomes exactly equal to one, then the value of the transparency coefficient reaches the absolute maximum, that is, one. For the zero angle of incidence of quasiparticles on the barrier, the Klein paradox phenomenon is observed, i.e, the quantum transparency of the system is perfect, and this is right for any values of the parameters a, (3, U, E. For certain ratios of particle energy E, the barrier height U and the magnitude of p there is the supertunneling phenomenon, which is that under these conditions the transmission coefficient is equal to one independently of the angle of incidence of the particles on the barrier. Characteristic of the transmission spectra T(E) is also the presence of a critical angle of incidence and a gap of energies. У рамках континуального підходу розраховано і проаналізовано коефіцієнт трансмісії Т діраківських квазіелектронів крізь сходинкоподібний потенціальний бар’єр в а-Тз моделі. Вважається, що ступінь зв’язку центрального атома з атомами у вершинах гексагональної гратки характеризується параметром а, який може набувати значення від нуля до одиниці. Особливу увагу приділено проміжним значенням а, оскільки, як відомо з літератури, вони є важливими для спостереження низки фізичних явищ. Хвильові функції, а також коефіцієнт трансмісії визначено за допомогою рівняння діраківського типу. Гамільтоніан системи представлено спінором із дев ’яти компонентів, які виражаються, зокрема, через параметр а. Коефіцієнт трансмісії знайдено за допомогою зшивання хвильових функцій на гетеромежах. З ’ясовано, зокрема, що існує область параметрів задачі, таких як висота електростатичного бар ’єру U, енергія квазіелектрона Е, відношення швидкостей Фермі в бар ’єрній і позабар ’єрній областях Д в якій значення коефіцієнта трансмісії досягає максимуму, тобто наближається до одиниці, для близьких до одиниці значень а. В цій області залежність коефіцієнта трансмісії від величини а є слабкою. Коли величина а стає точно рівною одиниці, то і значення коефіцієнта прозорості досягає абсолютного максимуму, тобто одиниці. Для нульового кута падіння квазічастинок на бар ’єр спостерігається явище клей- нівського парадоксу, тобто квантова прозорість системи є ідеальною, і це справедливо для будь-яких значень параметрів а, Д, U, Е. Для певних співвідношень енергії частинок Е, висоти бар’єру U і величини Д має місце явище супертунелювання, яке полягає в тому, що для заданих умов коефіцієнт трансмісії дорівнює одиниці незалежно від кута падіння частинок на бар’єр. Характерніш для трансмісійних спектрів Т(Е) є також наявність критичного кута падіння та забороненої зони енергій.
Keywords: step-like barrier; transmission spectra; сходинкоподібний бар’єр; спектри трансмісії; кафедра фізики та професійної безпеки